2022
DOI: 10.1007/s00520-021-06784-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between a sense of connection and existential and psychosocial outcomes in gynecologic and breast cancer survivors

Abstract: Background A cancer diagnosis may lead to existential despair but potentially also to perceived inner growth. This growth may be fostered through meaningful connections with others. We sought to describe existential and related psychosocial outcomes and their association with a sense of connection with others in individuals with gynecological and breast cancers. Methods We used cross-sectional data from two ongoing cohort studies of gynecologic ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This level of connection is deeper the more the two people matter to each other. Such connections have proven to be therapeutic and provide positive spiritual/existential outcomes (Jewett et al, 2022).…”
Section: Relational Spiritual Carementioning
confidence: 99%
See 1 more Smart Citation
“…This level of connection is deeper the more the two people matter to each other. Such connections have proven to be therapeutic and provide positive spiritual/existential outcomes (Jewett et al, 2022).…”
Section: Relational Spiritual Carementioning
confidence: 99%
“…This level of connection is deeper the more the two people matter to each other. Such connections have proven to be therapeutic and provide positive spiritual/existential outcomes (Jewett et al, 2022). This first level of spiritual care is "spiritually conscious care" (Saunders et al, 2010, p. 355) that can "be easily implemented in everyday health-care practice" (Henoch & Danielson, 2009, p. 229).…”
mentioning
confidence: 99%
“…In those coping with medical illness, there can also be a reciprocal relationship between psychological and physical well-being, such that unresolved psychological loss may diminish health outcomes, which then further increases psychological suffering. Loneliness in cancer patients may deteriorate quality of life because the lack of meaningful relationships can be demoralizing [9]. Loneliness has been associated with depression, poor immune function, pain, and fatigue in cancer survivors [10].…”
Section: Lonelinessmentioning
confidence: 99%
“…These characteristics of cancer lead people to re-examine priorities, relationships, and themselves, providing opportunities for positive psychological change 7 , 8 , such as post-traumatic growth (PTG). Studies have provided empirical evidence that post-traumatic growth is observed in women with gynecological cancer 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%